Sociological Intervention «a la polonaise»: Alain Touraine’s Method in the Polish Context - Frybes, Marcin (Przegląd Socjologii Jakościowej, 2019)
In 1981, the French sociologist Alain Touraine (with a group of Polish young sociologists led by the veteran of Polish sociology – Jan Strzelecki), conducted a famous research on the Solidarity Movement with the use of a new and distinct method of investigation called “sociological intervention.” It was the first time that Polish sociologists, who were trained in a specific combination of Marxist and positivist traditions, had experienced this kind of ‘hard’ qualitative methodology. The reactions were mixed and the general approach was rather cautious. Nevertheless, the sociological intervention method has since been used several times by Polish scientists. The aim of this paper is to summarize these experiences.